Financial Participation In Poland In Comparison To Other EU Countries - Kozłowski, Maciej (Comparative Economic Research. Central and Eastern Europe, 2015)
The success of the profound restructuring changes in the Polish economy depended mainly on the effectiveness of the reforms concerning the restructured properties in all sectors. This required a new approach to private property, determining the new role and place of employees in the process of changes and forming employee companies. Employee companies were formed as a result of direct privatization, so-called liquidation, when the equity of the enterprise is handed over for use with the right to the repurchase by the majority of employees of the established company (leasing). Prior to this privatization it was necessary to convince employees to purchase shares. One should keep in mind that this method turned out to be effective with respect to small and medium-sized enterprises, which didn't require the great financial outlays which were necessary for the privatization of larger companies. Initially it may be said that the conditions for implementing new solutions increasing the participation of employees in ownership, or their participation in other financial programs, are not very favourable. It is even possible to formulate the thesis that in Polish enterprises and amongst employees, peculiarly at the workshop level, there was an awareness barrier, which has made the process of further democratic changes rather difficult. Breaking this barrier can only take place after a certain time, when the employee as an owner begins to understand the economic significance of a dividend, picks up the habit of thinking in categories of an increase in goodwill, and realizes that this is transferred directly into an increase in the value of his or her assets.